Diffusions generated by the Wiener process - Bigun, G.S.; Osypchuk, M.M. (Carpathian Mathematical Publications, 2013)
The article concerns the possibility ofmaking a diffusion process in $\mathbb R^m$ by converting theWiener process. Here we apply a smooth transformation of phase space and random time substitution with the help of additive functional of integral type.